FAKTOR PERILAKU YANG MEMPENGARUHI TERJADINYA KEPUTIHAN PADA REMAJA PUTRI - Egi Yunia Rahmi; Arneliwati ' '; H. Erwin ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research is to know behavioral factors that influence whiteness in women teenagers. The method of the research used correlation description with cross sectional approach.The research has done at 82 respondents in SMA Negeri 1 Rumbio Jaya using total sampling technique. The assessment thatusedquisioners.The analyze thatusedbivariat analyze using Chi Square test. The result of the research shows that there is no correlation between women teenagers knowledge and attitude level towards whiteness and for responds got p value =0,041 where p value < 0,05, it can be concluded that there is correlation between respondents respond towards whiteness.This research result is hoped can be seen for women teenagers to more be attention the problem health that happened in them especially about whiteness. Key words: knowledge, attitude, respond, whiteness